Il mare come metodo? Suggestioni dall’Oceano Indiano - Raffaele Maddaluno (Archivio Antropologico Mediterraneo)
The features of movement, fluidity, indeterminacy arise as an expression of the materiality of the sea and at the same time as an imaginative tank with which to rethink binary, terrestrial, crystallised logics. This contribution traces several approaches that look at the materiality of the sea in its perturbative and imaginative dimension, in order to put them in dialogue with the literature that looks at the Indian Ocean as a cultural continuum; the aim is to disclose the preponderance of the oceanic context and its intrinsic traits in connecting and shaping knowledge, cultures and imaginaries. From the Indian Ocean, the intention is therefore to think of the sea as an (anti-) method, dwelling on those characteristics of movement, fluidity, disorder as axioms with which to reinterpret the unforeseeability of encounters, hybridisations, as well as historical and cultural processes.